1983
DOI: 10.1016/0736-5748(83)90007-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute‐phase α2‐macroglobulin in csf during development of the fetal rat

Abstract: The concentration of acute phase α2-macroglobulin (APα2M) was measured in the cerebrospinal fluid (csf) and plasma of fetal (12-22 days gestation) and neonatal (0-10 days post partum) rats. APα2M was detectable in the fetus as early as samples could be obtained (12 days) and increased in both fluids to reach a peak near the time of birth (17 mg/100 ml in csf and 168 mg/100 ml in plasma). During the neonatal period APα2M concentration declined markedly in both fluids. The results are compared with values for al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…This large variation in apparent blood-CSF permeability between similar sized proteins provides clear evidence that all three are unlikely to be transferred into the CSF by a common mechanism based on diffusion. A similar conclusion can be drawn from the reports by Dziegielewska, Evans, Lai, Lorscheider, Malinowska, M0llgard & Saunders (1981) and Panrucker, Dziegielewska, Lorscheider & Saunders (1983) on rat CSF/plasma ratios during development, but the published data are less complete than for fetal sheep (see also Discussion). In addition, at 60 days gestation in the fetal sheep, it was found that sucrose (0 5 nm molecular radius) which is often used as an inert marker for diffusion studies, reached a steady-state CSF/plasma ratio that was not significantly different from the endogenous sheep albumin ratio, despite a 6-fold difference in their molecular sizes .…”
Section: Introductionsupporting
confidence: 82%
“…This large variation in apparent blood-CSF permeability between similar sized proteins provides clear evidence that all three are unlikely to be transferred into the CSF by a common mechanism based on diffusion. A similar conclusion can be drawn from the reports by Dziegielewska, Evans, Lai, Lorscheider, Malinowska, M0llgard & Saunders (1981) and Panrucker, Dziegielewska, Lorscheider & Saunders (1983) on rat CSF/plasma ratios during development, but the published data are less complete than for fetal sheep (see also Discussion). In addition, at 60 days gestation in the fetal sheep, it was found that sucrose (0 5 nm molecular radius) which is often used as an inert marker for diffusion studies, reached a steady-state CSF/plasma ratio that was not significantly different from the endogenous sheep albumin ratio, despite a 6-fold difference in their molecular sizes .…”
Section: Introductionsupporting
confidence: 82%
“…Although there is a general tendency for the csf: plasma ratio to fall with increasing fetal age the pattern of fall was different for each protein (cf. Table 1, Panrucker et al 19 and Table 2). For example, the transferrin csf:plasma ratio decreased from 10.4 to 5.7% between 22 days and the newborn whereas that of albumin did not change; ~2 etamacroglobulin increased significantly and a-fetoprotein decreased, but only slightly, during the same period.…”
Section: Discussionmentioning
confidence: 94%
“…The pattern of change in transferrin concentration in fetal rat csf at different ages is similar to that previously described for albumin 12 and et2-macroglobulin. 19 The concentrations of all 3 proteins increased progressively after 15 days gestation to reach a peak on the day of birth. AFP reached its peak concentration in csf at 17-19 days ~5 and had declined to less than half the peak by the newborn period.…”
Section: Discussionmentioning
confidence: 97%
“…The detection of ca2M mRNA in neuronal tissues may explain the presence of a2M in cerebrospinal fluid of rat fetuses as described by Panrucker et al (1983b). In order to identify the type of cells responsible for the a2M mRNA synthesis in brain, the in situ hybridization should be carried out with a 3Hor 35Slabelled probe to achieve a higher resolution.…”
Section: Discussionmentioning
confidence: 99%